Lemon essential oil; the organic insect repellent - Mohd Noor, Siti Fatimah; Muhamad, Aida; Abdul Halim, Norhazimah; Amri, Muhammad Akmal; Shaari Majed, Muhammad Amer Daneal; Abdullah, Dzul Izlee (Penerbit UTHM, 2020)
Commercial insecticides are widely used in most sectors of the agricultural production to avoid or reduce losses by insects and hence it can improve the production as well as the quality of the product produced. In some ways, it can also improve the value of food and also its safety. Insecticides can be considered as an economic, labour-saving and efficient tool of insect management in agricultural production [1].